Schools as platforms for youth participation and agency through citizenship education: school strategies and young people’s perception (Revista Lusófona de Educação, 2025)
Studies in education have drawn attention to the importance of developing democratic skills in young people through citizenship education, confirming the fundamental role of public schools in the personal and social development of young people. Emphasis has also been placed on the importance of an approach to citizenship education that encompasses experiential dimensions and is based on experiential learning, as well as the value of participatory approaches to the promotion of these skills. This article, the result of a mixedmethodsstudy, seeks to understand how schools emerge as platforms for the civic and political participation of young people by analysing school guidance documents, semi-structured interviews with teachers coordinating citizenship education, and a questionnaire distributed to young secondary school students. The results point to a diversity of strategies led by different educational actors that schools develop with the aim of involving students civically and politically, either by promoting community initiatives or by promoting youth participation in the school environment. In addition, young people’s perceptions show that these actors value more participatory approaches to citizenship education in their school contexts.Keywords: citizenship education; youth participation; rural schools; secondary education